Prenatal Diagnosis of 17p11.2 Copy Number Abnormalities Associated With Smith–Magenis and Potocki–Lupski Syndromes in Fetuses - Cai, Meiying; Fu, Xianguo; Xu, Liangpu; Lin, Na; Huang, Hailong (Frontiers in Genetics, 2021)
Smith-Magenis syndrome (SMS) and Potocki-Lupski syndrome (PTLS) are rare autosomal dominant diseases. Currently, clinical phenotypes of adults and children have been reported, while fetal ultrasonic phenotypes are rarely reported. A retrospective analysis of 6200 pregnant women who received invasive prenatal diagnosis at Fujian Provincial Maternal and Child Health Hospital between October 2016 and January 2021 was performed. Amniotic fluid or umbilical cord blood was extracted for karyotype analysis and single nucleotide polymorphism array (SNP-array). SNP-array revealed six fetuses with copy number variant (CNV) changes in region 17p11.2. Among them, one had CNV microdeletion in the 17p11.2 region, which was pathogenically analyzed and diagnosed as SMS. Five fetuses had CNV microduplication in the 17p11.2 region, which was pathogenically analyzed and diagnosed as PTLS. Prenatal ultrasound phenotypes of the six fetuses were varied. The parents of two fetuses with PTLS refused pedigree verification. One fetus with SMS and one fetus with PTLS were confirmed as de novo by pedigree. PTLS in two fetuses was confirmed to be from maternal inheritance. Prenatal ultrasound phenotypes of SMS and PTLS in fetuses vary, SNP-array is a powerful diagnostic tool for these diseases. The ultrasonic phenotypes of these cases enrich the clinical database.